Disturbance‐mediated facilitation by an intertidal ecosystem engineer. Issue 9 (2nd August 2017) - Wright, Jeffrey T.; Gribben, Paul E.
Abstract: Ecosystem engineers facilitate communities by providing a structural habitat that reduces abiotic stress or predation pressure for associated species. However, disturbance may damage or move the engineer to a more stressful environment, possibly increasing the importance of facilitation for associated communities. In this study, we determined how disturbance to intertidal boulders (i.e., flipping) and the subsequent movement of a structural ecosystem engineer, the tube‐forming serpulid worm Galeolaria caespitosa, from the bottom (natural state, low abiotic stress) to the top (disturbed state, high abiotic stress) surface of boulders influenced the importance of facilitation for intertidal communities across two intertidal zones. Theory predicts stronger relative facilitation should occur in the harsher environments of the top of boulders and the high intertidal zone. To test this prediction, we experimentally positioned boulders with the serpulids either face up or face down for 12 months in low and high zones in an intertidal boulder field. There were very different communities associated with the different boulders and serpulids had the strongest facilitative effects on the more stressful top surface of boulders with approximately double the species richness compared to boulders lacking serpulids. Moreover, within the serpulid matrix itself there was also approximately double the species richness (both zones) and abundance (high zone only) of small invertebrates on the top of boulders compared to the bottom. The high relative facilitation on the top of boulders reflected a large reduction in temperature by the serpulid matrix on that surface (up to 10°C) highlighting a key role for modification of the abiotic environment in determining the community‐wide facilitation. This study has demonstrated that disturbance and subsequent movement of an ecosystem engineer to a more stressful environment increased the importance of facilitation and allowed species to persist that would otherwise be unable to survive in that environment.